(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2026)
One of the pressing challenges of medical rehabilitation today is not only the treatment of the primary pathology, but also the elimination of the resulting disorders at all integrative levels of the body’s functioning, restoration of functional capacity for living conditions familiar before the onset of the disease, achievement of social and professional adaptation, and improvement of quality of life. Finding solutions to this problem is relevant for patients with gastroesophageal reflux disease. Reflux disease, which is recognized as the leading disease of the digestive system due to its frequency, potential severe clinical manifestations, and consequences. The clinical picture of GERD is multifaceted and can manifest and be complicated by extraesophageal manifestations. Numerous studies indicate the widespread prevalence of bronchopulmonary pathology in patients with GERD. According to the literature, 34-60% of patients with GERD have chronic obstructive pulmonary disease. Two mechanisms are recognized as the main causes of chronic obstructive pulmonary disease in GERD: microaspiration of gastric contents into the bronchi and reflex etiology of pulmonary manifestations through the vago-vagal Reflex. Extraesophageal manifestations of GERD are often not associated by patients and physicians with gastrointestinal pathology, which can lead to inappropriate management strategies. Medication plays a key role in GERD treatment. The highest cure rates and maintenance of remission are achieved with combination therapy with proton pump inhibitors and prokinetic agents . Long-term use of these agents increases the risk of various complications, which are often unacceptable to the patient. Therefore, non-pharmacological approaches are increasingly becoming important in the comprehensive treatment of GERD.